WRELADS - The Australian Laser Depth Sounding System - Calder, M. (The International Hydrographic Review, 2015)
In 1972 in response to a request from the Royal Australian Navy, the Weapons Research Establishment of the Department of Supply began investigations into techniques that might be employed to increase the speed, and reduce the cost, of conducting hydrographic surveys of Australia’s Continental Shelf. Resulting from these investigations it was apparent that only airborne laser techniques gave promise of any substantial manpower and cost economies while at the same time providing positive validation of data obtained. Initially the target was to produce a system with an assured depth measuring capacity of about 30 metres in clear water, an accuracy in depth of one metre or better, a complete swept path of at least 200 metres and a speed of advance of 100 knots; navigational accuracy was to equal that currently obtained with medium range radio position fixing systems. So far all these requirements have either been met or bettered. This paper firstly highlights the problem confronting the Royal Australian Navy’s Hydrographic Service; it then traces the history of the WRELADS project as it is now known, through the initial development of a profiling prototype (WRELADS I) to the current scanning prototype (WRELADS II). The current state of development is fully described and further development milestones leading to an expëcted “ in service” date of June 1981 are discussed. The paper then details the concept of operations with an example of a proposed practical application of these concepts and concludes with a brief statement regarding the incorporation of WRELADS data into the Hydrographic Office data bank and an identification of currently unresolved problems.